High prevalence and characterization of extended-spectrum ß-lactamase producing Enterobacteriaceae in Chadian hospitals - Ouchar Mahamat, Oumar; Lounnas, Manon; Hide, Mallorie; Dumont, Yann; Tidjani, Abelsalam; Kamougam, Kadidja; Abderrahmane, Madina; Benavides, Julio; Solassol, Jérôme; Bañuls, Anne-Laure; jean-Pierre, Hélène; Carrière, Christian; et al. (BMC infectious diseases, 2019)
Extended-spectrum ß-lactamase-producing Enterobacteriaceae (ESBL-PE) represent a major problem in the management of nosocomial infections. However, ESBL-PE are not systematically monitored in African countries. The aim of this study was to determine ESBL-PE prevalence in patients from three hospitals in N'Djamena, the capital city of Chad, and to characterize the genetic origin of the observed resistance. From January to March 2017, 313 non-duplicate isolates were recovered from various clinical specimens obtained from 1713 patients in the three main hospitals of N'Djamena. Bacterial species were identified by matrix-assisted laser desorption ionization-time of flight mass spectrometry. Susceptibility to 28 antibiotics was tested using the disk diffusion method on Müller-Hinton agar, and ESBL production was confirmed with the double-disc synergy test. The most prevalent ESBL genes associated with the observed resistance were detected using multiplex PCR followed by double-stranded DNA sequencing. Among the 313 isolates, 197 belonged to the Enterobacteriaceae family. The overall ESBL-PE prevalence was 47.72% (n = 94/197), with a higher rate among inpatients compared with outpatients (54.13% vs. 34.37%). ESBL-PE prevalence was highest in older patients (≥60 years of age). E. coli was the most common ESBL-producer organism (63.8%), followed by K. pneumoniae (21.2%). ESBL-PE were mainly found in urine samples (75%). The CTX-M-1 group was dominant (96.7% of the 94 ESBL-PE isolates, CTX-M-15 enzyme), followed by the CTX-M-9 group (4.1%). 86% of resistant isolates harbored more than one ESBL-encoding gene. ESBL production was also associated with the highest levels of resistance to non-β-lactam drugs. The prevalence of ESBL-PE harboring resistant genes encoding ESBLs of the CTX-M-1 group was high (48%) among clinical isolates of three main hospitals in Chad, suggesting an alarming spread of ESBL-PE among patients.